Analisis Daya Saing Finansial Antar Bank Pada Perbankan Syariah di Indonesia - Hijrasil Hijrasil; Zandy Pratama (Journal Economic Excellence Ibnu Sina, 2024)
This research aims to measure the competitiveness of sharia banks in Indonesia. The sharia banks in this research are Sharia People's Bank and My Syariah Bank. The method used in this research is comparative descriptive. The results of the research show that the level of competitiveness of Islamic banks is based on the bank's health level, through measuring financial ratios. Bank Rakyat Syariah has a better bank health level than My Bank Syariah.